Heavy metal-immobilizing bacteria combined with calcium polypeptides reduced the uptake of Cd in wheat and shifted the rhizosphere bacterial communities. (December 2020) - Han, Hui; Wu, Xuejiao; Yao, Lunguang; Chen, Zhaojin
Abstract: In situ stabilization techniques for the "remediation" of heavy metal-contaminated soil are a novel and inexpensive technology. However, the mechanisms underlying the interaction of exogenous passivators with the bacterial community in wheat rhizosphere soil remain unclear. Soil static culture and pot experiments were conducted to evaluate the effects and mechanisms of the heavy metal-immobilizing bacterium Enterobacter bugandensis TJ6 and calcium polypeptides (CPPs) and their association with Cd uptake in wheat, soil quality and the rhizobacterial community structure. The results showed that compared with the control treatment (CK), the TJ6, CPP, and TJ6+CPP treatments significantly decreased the diethylenetriaminepentaacetic acid (DTPA)-extractable Cd (25.2%–60.1%) content and increased the pH, organic matter content and urease activity in the wheat rhizosphere soil, which resulted in decreases in the Cd (21.5%–77.8%) content in wheat tissues (grain, straw, and roots). In particular, the TJ6+CPP treatment was more effective at decreasing Cd accumulation in grains. Furthermore, the TJ6+CPP treatment improved the diversity of the soil bacterial community in the wheat rhizosphere, and the relative abundances of Proteobacteria, Firmicutes, Arthrobacter, Microvirga, Ensifer, Brevundimonas, Devosia and Pedobacter were enriched. These results suggest that the TJ6+CPP treatment decreased the uptake of Cd in wheat by i) providing essential elements (N and C sources), ii) increasing the pH and reducing the bioavailable Cd content in wheat rhizosphere soil, iii) allowing colonization to promote plant growth and Cd-resistant bacteria, and iv) increasing the abundance of genes associated with ABC transporters, carbon metabolism and oxidative phosphorylation in the rhizosphere bacterial community. Our results showed that the heavy metal-immobilizing bacterium TJ6 combined with CPPs decreased the Cd content and increased the bacterial community diversity of wheat rhizosphere soil. Our results also highlight the potential of using heavy metal-immobilizing bacteria and CPPs to ensure the safe production of crops growing on heavy metal-polluted soils. Graphical abstract: Image 1 Highlights: E. bugandensis TJ6 immobilized Cd by bioprecipitation and extracellular adsorption. Strain TJ6 combined with CPPs reduced Cd accumulation in the wheat grain. Bioavailability of Cd was negatively correlated with pH, OM and NH4 + /NO3 − ratio. Proteobacteria and Firmicutes were involved in Cd immobilization. Abundance of gene associated with oxidative phosphorylation was increased in soil.